2023
DOI: 10.1093/qje/qjad026
|View full text |Cite
|
Sign up to set email alerts
|

Buyers’ Sourcing Strategies and Suppliers’ Markups in Bangladeshi Garments

Abstract: We study differences in markups earned by Bangladeshi garment exporters across buyers with different sourcing strategies and make three contributions. First, we distinguish buyers with a relational versus a spot sourcing strategy and show that a buyer’s sourcing strategy is correlated across products and origins. Buyer fixed effects explain most of the variation in sourcing strategies, suggesting that these depend on organizational capabilities. Second, we use novel data that match quantities and prices of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…For example, Bangladesh produces almost 98 categories of apparel products aggregated with two-digit HS codes, but the maximum revenues come from only a few products [35]. Cajal-Grossi et al [14] identified seventeen major woven products that cover most woven apparel exports. As a result, we treat the major seventeen woven products as the top woven products (these include the following HS6 products: 620341, 620342, 620343, 620349, 620461, 620462, 620463, 620469, 620510, 620520, 620530, 620590, 620610, 620620, 620630, 620640, 620690) and all the others as the benchmark woven products.…”
Section: Heterogenous Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bangladesh produces almost 98 categories of apparel products aggregated with two-digit HS codes, but the maximum revenues come from only a few products [35]. Cajal-Grossi et al [14] identified seventeen major woven products that cover most woven apparel exports. As a result, we treat the major seventeen woven products as the top woven products (these include the following HS6 products: 620341, 620342, 620343, 620349, 620461, 620462, 620463, 620469, 620510, 620520, 620530, 620590, 620610, 620620, 620630, 620640, 620690) and all the others as the benchmark woven products.…”
Section: Heterogenous Impactsmentioning
confidence: 99%
“…Due to government cash incentives and subsidized rate credit facilities, the backward linkage of the knit apparel industry has expanded in recent years [12]. However, due to the capital intensity of woven fabric production [13], this sector has remained underdeveloped despite its recent inclusion in cash incentive plans, which has led to the reliance of woven apparel production almost entirely on imported inputs from abroad [14], especially from China. Studies show that more than 50% of woven fabrics come from China [5], which is also evident in our data.…”
Section: Introductionmentioning
confidence: 99%
“…analyzes the role of imperfect contracts in the textile, pharmaceutical and cement sectors in Equador depending on market power. Most informative for our modeling (see Section 2.2.1),Cajal-Grossi et al (2020) show that suppliers in the Bangladeshi garment sector obtain higher prices when selling to relational buyers than when selling to spot buyers.3 Both surveys (e.g.,O'Rourke, 2005, andLoureiro andLotade, 2005) as well as field experiments with real purchasing decisions (e.g.,Smyth, 2011, andHainmueller et al, 2015) suggest that consumers do care about the ethical content of their consumption and in fact have a higher willingness to pay for 'ethical' products.…”
mentioning
confidence: 99%